Venture Survival in a Transitional Economy - Lyles, Marjorie A.; Saxton, Todd; Watson, Kathleen (Journal of Management, 2004)
Many formerly controlled economies have undergone discontinuous transformations in their approach to markets, institutional environments, and the role of government in economic activity. We study the factors that affect venture survival in a transitional economy through a two-stage study of private ventures in Hungary. We find that ventures survive under uncertainty, even without significant government support. Industry experience, networking activities, and the strategic orientation of the firms predict survival. Contrary to our predictions, SOE experience, access to infrastructure, and differentiation strategies do not significantly differentiate survivors.